About lost futures or the political heart of history - Mudrovcic, Maria Ines (2014)
The consideration that our era lives under the sign of memory and that this has become the main concern of culture in western societies is a commonplace. This shift to the past has been described as a “memory boom”,2 a “surfeit of memory”,3 a “world (that is) being musealised”4 and as a “desire to commemorate”.5 This “obses sion with recalls” has been interpreted in many studies: on local, cultural or “from below” mem ories, on ways of keeping memories (from me morials and monuments to files, movies, biog raphies and commemorations, etc), on ways of understanding a historiography that looks back to the recent past, about politics of memory and past uses, among other issues. These studies have multiplied in the most varied disciplines, including, sociology, social psychology, history, psychoanalysis, neurobiology, culture sociolo gy, philosophy, etc. The diagnosis seems to be unanimous: we are living in a period in which the present lives off the past, in a kind of “a present past”,6 with the result that we lapse into what Hartog calls “presentism”. This past that lives in the present has been called “traumatic”,7 “sub lime”,8 “espectral”,9 among others. We are expe riencing a “new order of time”: “D’un coté ... un passé qui n’est pas aboli ni oublié, mais un passé duquel ne pouvons à peu prés rien tirer qui nous oriente dans le present et nous donne à imagi ner le future. De l’autre, un avenir sans la moin dre figure.”10 An order of time which casts doubts on the future understood as progress. It puts in question the modern regime of temporality; “in stead of being oriented towards the future, it is oriented towards the past”